Penggunaan Kalsium Hidroksida (Ca(OH)2) Dan Aluminium Sulfat ((Al2SO4)3) Untuk Pengolahan Air Limbah Settling Pond PT. Internasional Prima Coal - Fransiska Angelina Kusnanto; Shalaho Dina Devy; Agus Winarno (ReTII, 2023)
Acid mine drainage (AAT) is water formed at mining sites with a low pH (pH<6) as a result of opening up a potential for rock acidity, causing problems for water quality, and rocks containing sulfide minerals. The purpose of this study was to determine the effect of using calcium hydroxide (Ca(OH)2) and aluminium sulphate ((Al2SO4)3) at optimum doses on neutralizing pH and reducing metal content in AAT. This study used a variation of the dose of calcium hydroxide (Ca(OH)2) of 0,5; 0,75; 1; and 1,25 grams and the variation of the dose of aluminium sulphate ((Al2SO4)3) of 1; 1,75; 2,5; and 3,25 grams with a contact time of 30 minutes. The initial concentration of TSS acid mine drainage was 430 mg/L, Fe was 26,92 mg/L, Mn was 7,69 mg/L, and pH was 3,8. The results showed that the doses of calcium hydroxide (Ca(OH)2) and aluminium sulphate ((Al2SO4)3) had an effect on Ph, TSS, Fe, and Mn. TSS removal efficiency was 96,89%, Fe was 99,74%, and Mn was 95,19%.